Competition law on media plurality: a comparitive study between Malaysia and the United Kingdom / Abu Zufar Abu Zarim...[et al.] - Abu Zarim, Abu Zufar; Shuhaimi, Nur Aisyah; Abd Hamid, Abdul Hakim; Damanhoori, Lyyana (Faculty of Law, 2013)
As of the year 1945, United Kingdom demonstrated a steadfast pledge to preserving media plurality. United Kingdom gave significant importance to competition law as a means of encouraging media pluralism. Malaysia, on the other hand, has recently implemented the Competition Act 2010. Its aims are to protect the competitive process for the benefit of businesses, consumers and the economy. This paper will first look at the implementation of the competition laws in the United Kingdom with regards to ensuring media plurality. Secondly, it offers the application of the Malaysian Competition Act 2010. Thirdly, it will review and compare both jurisdictions on the application of competition law with regards to safeguarding media plurality. Finally, it will conclude its findings and suggest recommendations